Drill String Modeling and Stress Analysis - Abdul-Ameer, A. (2012)
The unsupported deflection of drill strings which are subjected to increasing gravitational loading and distortion, with borehole depth and twisting, is considered. Eccentric loading configurations which include the lateral reaction to mud flow pressure, compression, bending forces and twisting moments are incorporated in the derivations. The bending- buckling deflections and twist angle dynamics following drill string drive motor voltage changes are provided. The principal stress level is identified when operating at particular borehole depths and with specified cutting velocities.